The relationship between the strength of pain and verbal expressions of pain (Sensory / Emotional) Study of Correlation Among a Sample of Breast Cancer Patients in Lattakia - Mohamad, Hala; Ghanem, Lina (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed to examine the relationship between the strength of pain and expressions of pain among a sample of breast cancer patients in Latakia, and examine the relationship between the strength of pain and sensory expressions of pain, and to examine the relationship between the strength of pain and emotional expressions of pain. Participants were (50) patient from breast cancer patients. The measures were EVA to strength of pain and Saint - Antoine scale to assess pain. The results showed that there is correlation the strength of pain and expressions of pain among the members of the sample as a whole, and correlation the strength of pain and sensory and emotional expressions of pain.